Do convento a um barraco na “Planeta dos Macacos”: a participação das irmãs Beneditinas da Virgem Maria no movimento político de organização social das favelas do Recife (1970-1980) - Silva, Severina Madalena da (2018)
The focus of this research was the investigation of the participation of the Catholic Church through the engagement of a group of sisters and postulants of the Congregation of the Benedictines of the Virgin Mary in the Slum Movement active in the mid-70s and 80s of the 20th century in the region Metropolitan of Recife, focusing on the community now known as Planet of the Apes, located in the neighborhood of Jardim São Paulo. It sought to discern the dialogical relationship between the social challenges of that moment and the symbolic contents of the Catholic religion, as interpreted and lived during the episcopate of Dom Helder Pessoa Camara (1964- 1985). The question that was asked was how the Congregation of the Benedictine Sisters of the Virgin Mary was involved, through non-assistential social actions, in the transformation of an occupation into a community, in the troubled political scenario that was our country. For this, bibliographical research was used, with authors representing Liberation Theology, and the exploitation of documentary and imagery records deposited over the years in the archives of the Community Center of the Planet of the Apes Community.